STUDY OF KARONESE AFFIXATION IN FORMING VERB - Oktavianus Oktavianus; Zainuddin Zainuddin (State University of Medan, 2012)
ABSTRACT This study deals with affixation of Karo Language in forming verb. The objectives of this study are to describe the morphological process of affixation in forming verbin Karo language as well as to describe the function and the grammatical meanings of affixation in forming verb in Karo language. The method of research is library research by reading some books related to this study. The instruments of collection data used tape recorder. The technique of analysis data is documentary technique namely identifying the data, classifying the data and finding the dominant type of affixation in Karo language. The findings showed that there are four kinds of Karonese affixation in forming verb namely: (1). Prefix occurs 51 (48%). (2). Infixes occurs 3 (2%), (3). Suffixes occurs 43 (30%) and (4). Confixes occurs 18 (10%) and the total occorences is 119. So the dominant type of affixation found in Karonese in forming verb is Prefix occurs 51(48%). The function of affixation in Karo language are derivational and inflectional, derivational is change the meaning after attached by affix to the stem for example: er- + lajang → /erlajang/, /lajang/ means ‘alone’, prefix er- is inserted, it becomes /erlajang/ means ‘going’ and inflectional is does not change the meanings after attached by affix to the stem for example: ayak + -i → /ayaki/ , /ayak/ means ‘running’, suffix -i inserted, it becomes /ayaki/ means “running” . The grammatical meanings of affixation in Karo language in forming verb are process and activity for example /ersada/ ‘gathered’ meaning of affix er- is as process and /erjuma/ ‘ farming’ meaning of affix er- is as activity .